SOLVING FRICTIONLESS CONTACT PROBLEMS IN SOLID MECHANICS USING SMOOTHED PARTICLE HYDRODYNAMICS - Pratama, Valdo
Smoothed Particle Hydrodynamics (SPH) is a Lagrangian meshless based computation method. This method is originally used for solving astrophysics problems, but nowadays it is also implemented for fluid and solid mechanics problem. In this project, SPH is applied to simulate a colliding two-dimensional modelled blocks where the sensitivity of its scaling factor is analyzed. The scaling factor is a components of the contact force. The contact force is located in the boundary particles of the model. From references, treatment of contact boundary conditions in SPH is still not perfect yet and development is still on-going. SPH technique is basically computing discretize structure domain into particle with certain defined or even calculated properties with a smoothing function which each neighboring particle will effect one another. In this project, the author will use SPH to simulate elastodynamics impact problem considering its contact algorithm.